(3PNjQI GdWGdH HeG GdeYde WGdH ef BOGH heBQHs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdPi gOi Cgd GdYde hHYO agPg jhGbjJ UOGf WdH GdYGde CaVd YfO Gddg ef GdUdGI hGdUjGe hGdML hGdLgGO ai SHjd Gddg s
(3BNQgG (B:s
(3Ydi cd hGMO ef GdYGde hGdeJYde Cf jTJZd HeG gh Cgde Ydjg eeG gh eCehQHg hdjLYd BNQ bhdg bHd bjGeI e cd eLdS ceG eQ SHMGfc Gddge hHMeOc CTgO Cf dG Edg GdG GfJ s
(3HgG WeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdSjGSI hGdGLJeGYs